Rancang Bangun Alat Penghantar Makanan Pintar - Subagja, Riki; Nurdiana, Nita; Al Amin, M Saleh (Universitas PGRI Palembang, 2022)
The COVID-19 pandemic has given rise to new habits where these new habits require people to keep their distance in all community activities and interactions. From this habit, the idea was born to design a prototype of a smart food delivery device. The purpose of this research is to design a device that can help serve food automatically to the customer's table by relying on a conveyor as a mechanical device that can move goods from one place to another and sensors and laser diodes as a plate position detection device. The design of this tool uses a conveyor that is positioned like a conveyor belt to deliver food. The LDR is used as a sensor to detect where the food stops receiving input from the laser diode. This sensor is placed facing the laser diode when food is placed on the conveyor table it will pass through the LDR and laser diode. Based on the results of the tests that have been carried out, this prototype requires a power of 0.593 Watt when the conveyor is without load and 1.142 Watt when the conveyor is loaded. Overall, the tool works as designedÂ AbstrakPandemi COVID-19 memunculkan kebiasaan baru dimana kebiasaan baru tersebut menuntut masyarakat untuk menjaga jarak dalam segala aktivitas dan interaksi masyarakat. Dari kebiasaan tersebut lahirlah ide untuk merancang sebuah prototipe perangkat pengantar makanan pintar. Tujuan dari penelitian ini adalah merancang suatu alat yang dapat memantu menyajikan makanan secara otomatis ke meja pelanggan dengan mengandalkan konveyor sebagai alat mekanis yang dapat memindahkan barang dari satu tempat ke tempat lain serta sensor dan dioda laser seagai alat pendeteksi posisi piring. Perancangan alat ini menggunakan konveyor yang diposisikan seperti ban berjalan untuk mengantarkan makanan. LDR digunakan sebagai sensor untuk mendeteksi di mana makanan berhenti menerima input dari dioda laser. Sensor ini diletakkan menghadap ke laser diode ketika makanan diletakkan di atas meja conveyor maka akan melewati LDR dan laser diode. Bedasarkan hasil pengujian yang telah dilakukan, prototipe ini membutuhkan daya sebesar 0,593 Watt saat conveyor tanpa beban dan 1,142 Watt saat conveyor berbeban. Secara keseluruhan, alat ini bekerja sesuai dengan perancangan